Influence of electrodeposited Cu-Ni layer on interfacial reaction and mechanical properties of laser welded-brazed Mg/Ti lap joints. (January 2019) - Auwal, S.T.; Ramesh, S.; Zhang, Zequn; Liu, Jinge; Tan, Caiwang; Manladan, S.M.; Yusof, F.; Tarlochan, F.
Abstract: A fiber laser welding-brazing procedure has been developed for joining AZ31B magnesium alloy to Cu-Ni coated Ti-6Al-4V titanium sheet using AZ92D filler wire. The effect of the interlayer arrangements (AZ31B/Ni-Cu/Ti-6Al-4V and AZ31B/Cu-Ni/Ti-6Al-4V) on appearance, interfacial reaction and mechanical properties were investigated at different heat input. It was found that the feasibility of this process depends strongly on the pre-existing Cu-Ni layer on the Ti surface that promotes wetting of the AZ92 filler. Within the range of 1200–1600 W, defect free joints in both interlayer arrangements. Depending on the interlayer arrangements chosen, different reactions layers formed inside the joint region. Nevertheless, at optimum heat input (1400 W), Ti2 Ni mingled with Ti3 Al interfacial reaction products was produced along the fusion zone (FZ)-Ti brazed interface in both interlayer arrangements. The tensile-shear fracture load of the joints produced at the optimum laser power reached a maximum value of 2016.5 N for AZ31B/Ni-Cu/Ti-6Al-4V and 2014.6 N for AZ31B/Cu-Ni/Ti-6Al-4V, representing an efficiency of 71% compared to AZ31B alloy. Under suitable heat input, the joints failed at the fusion zone of the AZ31B base metal. In contrast, incomplete brazing or large volume of intermetallics at the brazed interface resulted in interfacial failure at lower/higher heat input.